Resistance screening of white yam (Dioscorea rotundata Poir.) accessions against Meloidogyne incognita (Kofoid & White, 1919) Chitwood, 1949 using yam vines - Adomako, J.; Otoo, E.; Danso, Y.; Alhassan, D.K.; Adebola, P.O.; Asfaw, A. (University of Ljubljana, 2022)
Root-knot nematode (Meloidogyne incognita) is an economically important phytoparasitic nematode species. In yam production, therefore, breeding for nematode resistance is an important environmentally friendly tool to manage root-knot nematodes damage. The aim of this study was to determine the reaction of 18 yam accessions to M. incognita inoculation under screen house conditions using single node vine cuttings. Vines of each accession were planted in sterilized soil and inoculated with 1000 infective juveniles of M. incognita. Resistance level of yam accessions were based on both galling index score and reproductive factor. There were a significant differences in final infective stage nematodes population, galling index, reproduction factor and yield of mini tuber among the accessions tested. Sixteen (89 %) of the accessions showed moderate resistance (GI ≥ 2, Rf ≤ 1) to the test pathogen with two accessions classified as susceptible. Accession TDr1515OP16/0030 recorded the highest mini tuber yield mass of 19.4 g, which was 74 % higher than accession ‘TDr1515OP16/0108’ which recorded the lowest yield of 10.4 g. The moderately resistant accessions identified in the study can be utilized to reduce nematodes reproduction and help manage root-knot nematode in yam production.